Contra-ω-Continuous and Almost Contra-ω-Continuous - Ahmad Al-Omari; Mohd Salmi Md Noorani (International Journal of Mathematics and Mathematical Sciences)
The notion of contra continuous functions was introduced and investigated by Dontchev. In this paper, we apply the notion of ω-open sets in topological space to present and study a new class of called almost contra ω-continuous functions as a new generalization of contra continuity.